The type specimens of Paradisaeidae, Cnemophilidae and Ptilonorhynchidae (Aves) in the Museum für Naturkunde of the Humboldt-University of Berlin - Steinheimer, Frank D. (Zootaxa, 2005)
A comprehensive list of all type specimens of the manucodes and birds of paradise (Paradisaeidae), satin birds (Cnemophilidae) and bower birds (Ptilonorhynchidae) housed in the Museum für Naturkunde der Humboldt-University of Berlin (ZMB) is given, including those specimens considered to be paralectotypes and paratypes. Each entry discusses the history of the specimen, its nomenclature and taxonomy. The introduction gives a brief overview on ZMB registration numbers and a short history of research into avian types at the ZMB.